HOSPITALIZATION PATTERNS IN PATIENTS WITH UPPER GASTROINTESTINAL BLEEDING - VALERIY I. Podoluzhnyi; ORLAN V. Oorzhak; KONSTANTIN A. Krasnov (Фундаментальная и клиническая медицина)
Aim. To determine the hospitalization patterns in patients with upper gastrointestinal bleeding in Kemerovo.Materials and Methods. We analyzed the amount and structure of hospitalizations due to peptic ulcer disease, Mallory-Weiss syndrome, erosive gastritis, and liver cirrhosis in Kemerovo between 1997 and 2017. We compared two seven-year periods (2000-2006 and 2011-2017) or two decades (1997-2006 and 2007-2016). Results. Gastric/duodenal ulcers, Mallory-Weiss syndrome, erosive gastritis, and esophageal bleeding accounted for 64.5%, 18.9%, 9.7%, and 6.9% of hospitalizations, respectively. Time periods did not differ significantly in both number and prevalence of hospitalizations due to any of abovementioned disorders. However, the number of hospitalizations related to bleeding esoph-ageal/gastric varices and portal hypertension in-creased significantly (almost 2-fold for portal hypertension). Conclusions. Over the past 20 years, there has been no change in the average annual number of patients with bleeding gastroduodenal ulcers, Mallory-Weiss syndrome, and erosive gastritis. However, the number of hospitalizations due to a portal hypertension demonstrated an unacceptably high increase.